2022
DOI: 10.3390/admsci12040157
|View full text |Cite
|
Sign up to set email alerts
|

Development of Quality Digital Innovation by Optimally Utilizing Company Resources to Increase Competitive Advantage and Business Performance

Abstract: Purpose: This study aims to find out how to increase the competitive advantage of a company through the development of digital innovation that utilizes company resources optimally to improve business performance. Namely, the aim is to examine the effect of company resources on digital innovation and business performance, and the effect of company resources on business performance through digital innovation. Methods: This study uses a quantitative research approach. Observations were made in a cross-section/one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
(41 reference statements)
0
5
2
Order By: Relevance
“…By paying attention to these implications, it is expected that the development of MSME strategies will be more focused and support business performance. This study's results differ from the research conducted by Hidayat et al and Setyawati & Rosiana [7], [37] which state that competitive advantage positively and significantly affects business performance. The results of this study still need to be consistent to allow future researchers to conduct further research.…”
Section: The Effect Of Competitive Advantage On Business Performancecontrasting
confidence: 99%
“…By paying attention to these implications, it is expected that the development of MSME strategies will be more focused and support business performance. This study's results differ from the research conducted by Hidayat et al and Setyawati & Rosiana [7], [37] which state that competitive advantage positively and significantly affects business performance. The results of this study still need to be consistent to allow future researchers to conduct further research.…”
Section: The Effect Of Competitive Advantage On Business Performancecontrasting
confidence: 99%
“…The success of digital innovation depends on digital investment and resource support (Wicaksono et al, 2020). This was previously proven by Hidayat et al (2022) who found a significant influence of company resources on digital innovation in the ISP industry in Indonesia, which includes ISPs in the small category. Another finding by…”
Section: The Influence Of Company Resources On Digital Innovationmentioning
confidence: 84%
“…These aspects are classified as company resources (Thompson et al, 2020). Research shows that company resources influence digital innovation (Wicaksono, 2020;Hidayat et al, 2022;Hartono & Halim, 2020;Kiefer et al, 2021;Soluk, 2022;Lokuge & Duan, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The literature finds that SMEs engage in diverse activities to survive during a pandemic, such as adopting marketing or process innovation (El Chaarani et al 2021;Fabeil et al 2020;Rahman et al 2022), reducing employees or working hours reduction (Arslan et al 2022), adjusting supply networks (Fabeil et al 2020), and obtaining financial grants from the government or other external parties (Arslan et al 2022). Scholars also suggest that SMEs adopt digital technologies to improve their ability to survive (Adam and Alarifi 2021;Zutshi et al 2021) and capture broader customer markets as well as to improve business performance and gain competitive advantage (Hidayat et al 2022).…”
Section: Pandemic Impact On Smes and Their Survival Strategiesmentioning
confidence: 99%
“…The OECD (2021) report shows that 70% of SMEs are increasing their technology use for businesses compared to before the pandemic. Digital transformation improves SMEs' business performance through technology adoption, digital skills, and other strategies (Hidayat et al 2022;Teng et al 2022).…”
Section: Pandemic Impact On Smes and Their Survival Strategiesmentioning
confidence: 99%